Immune-enhancing activity of polysaccharides and flavonoids derived from Phellinus igniarius YASH1 - Xiaoya Zhu; Ruirui Guo; Xiayu Su; Kun Shang; Conglian Tan; Junheng Ma; Yuemeng Zhang; Dan Lin; Yueran Ma; Min Zhou; Jiale Yang; Qiqi Wu; et al. (Frontiers Media S.A., 2023)
Introduction:Phellinus igniarius (P. igniarius) (Sanghuang) is a widely used traditional Chinese medicine fungus, and its natural products have great potential for clinical application in immune enhancement. This study aimed to explore the immune-enhancing activity and underlying mechanisms of the polysaccharides and flavonoids derived from Phellinus igniarius (P. igniarius) and to provide a theoretical and experimental basis for the development of novel drugs.Methods: Wild P. igniarius YASH1 from the Loess Plateau in Yan'an region was collected, and polysaccharides and total flavonoids were extracted, isolated and identified from mycelium and sporophore. In vitro antioxidant activity was detected through the scavenging activity of hydroxyl radicals and total antioxidant capacity. Cell Counting Kit-8 and trypan blue detection kit were used to detect the effect of extract polysaccharides and flavonoids on the proliferation and phagocytosis ability of immune cells. To assess the effect of the drugs on cytokine secretion by immune cells and immune recovery in immunocompromised mice, the expression of interleukin (IL)-2, IL-6, interferon (IFN)-γ, and tumor necrosis factor (TNF)-α were examined at the cellular and animal levels. The species composition, abundance of gut microbiota and the altered content of short-chain fatty acids in the feces were analyzed to elucidate the possible mechanisms of drugs by 16S ribosomal RNA (rRNA) amplifiers sequencing and liquid chromatography-tandem mass spectrometry (LC-MS/MS).Results: Both polysaccharides and flavonoids derived from mycelium or sporophore had antioxidant activity and may stimulate the expression and secretion of IL-2, IL-6, and IFN-γ in immune cells while inhibiting TNF-α expression and secretion and increasing IL-2, IL-6, and IFN- γ expression levels in mice. Furthermore, polysaccharides and flavonoids from mycelium and sporophore showed different effects on the metabolic response of intestinal short-chain fatty acids (SCFAs) in mice, and the use of these drugs remarkably changed the species composition and abundance of intestinal flora in mice.Discussion: Polysaccharides and flavonoids from P. igniarius YASH1 mycelium and sporophore have in vitro antioxidant activity, and they affect the promotion of cell proliferation, stimulation of IL-2, IL-6, and IFN-γ secretion, and inhibition of TNF-α expression in immune cells. Polysaccharides and flavonoids from P. igniarius YASH1 may enhance immunity in immunocompromised mice and remarkably affect the intestinal flora and content of SCFAs.